Neutrophil extracellular trap formation in the Streptococcus suis‐infected cerebrospinal fluid compartment. (31st August 2016) - de Buhr, Nicole; Reuner, Friederike; Neumann, Ariane; Stump‐Guthier, Carolin; Tenenbaum, Tobias; Schroten, Horst; Ishikawa, Hiroshi; Müller, Kristin; Beineke, Andreas; Hennig‐Pauka, Isabel; Gutsmann, Thomas; Valentin‐Weigand, Peter; et al.
Abstract: Streptococcus suis is an important meningitis‐causing pathogen in pigs and humans. Neutrophil extracellular traps (NETs) have been identified as host defense mechanism against different pathogens. Here, NETs were detected in the cerebrospinal fluid (CSF) of S. suis ‐infected piglets despite the presence of active nucleases. To study NET‐formation and NET‐degradation after transmigration of S. suis and neutrophils through the choroid plexus epithelial cell barrier, a previously described model of the human blood‐CSF barrier was used. NETs and respective entrapment of streptococci were recorded in the "CSF compartment" despite the presence of active nucleases. Comparative analysis of S. suis wildtype and different S. suis nuclease mutants did not reveal significant differences in NET‐formation or bacterial survival. Interestingly, transcript expression of the human cathelicidin LL‐37, a NET‐stabilizing factor, increased after transmigration of neutrophils through the choroid plexus epithelial cell barrier. In good accordance, the porcine cathelicidin PR‐39 was significantly increased in CSF of piglets with meningitis. Furthermore, we confirmed that PR‐39 is associated with NETs in infected CSF and inhibits neutrophil DNA degradation by bacterial nucleases. In conclusion, neutrophils form NETs after breaching the infected choroid plexus epithelium, and those NETs may be protected by antimicrobial peptides against bacterial nucleases.